Educability, skills and parental involvement: a factorial analysis of teacher perception scale for families in psychosocial risk - Rodríguez Garcés, Carlos (2015)
Through the scale “Perception Teaching for Families Experiencing Psychosocial Risk” applied to 175 teachers in training, conducted an exploratory factor analysis (EFA). The AFE, with an explained variance of 43.9%, reveals the existence of four factors or dimensions: Implications Parental Education, features personological Attributive, Parental Participation and Attribution Genealogical. The subsequent descriptive analysis reports that there is a tarnished image by teachers of vulnerable children and their families. They are perceived to these low conditions for education, controversial personality and disinterest in their education make them highly susceptible to academic failure. Attributive features the familiar context of origin, glimpsing parents with a low level of parental involvement and competition.